The Technique of Formation of Valuable Attitude for Amateur Theatre by Future Leaders - Borzenko, Irina V.; Ignatova, Irina B.; Ilyenko, Natalia M.; Lyubimova, Natalia I.; Nikulina, Natalya N. (International Journal of Criminology and Sociology, 2022)
The dynamic development of theater culture in Russia, including the culture of Amateur theater, the growing popularity of Amateur theater in modern society, and the awareness of Amateur theater as a phenomenon of Russian national culture makes it urgent to improve the training of managers of Amateur theater groups in institutions of arts and culture. The study of literature, generalization of practical experience, and experimental research data led the authors to the conclusion that the direction of this improvement is to educate students in a value attitude to Amateur theater and their chosen profession. The functions of value attitude education: epistemological (knowledge), axiological (value), regulatory-normative and creative. Components of the pedagogical model: adaptive-diagnostic, planned-correctional, informational-activity, variative-creative, evaluative-effective. The results of the chosen pedagogical model gave positive results, which makes it possible to consider the proposed way to improve the training of specialists correct and appropriate.